The Strategic Assessment of Low-Carbon MICE Practices at Green Economy Expo (GEE) 2024 - Miranti Andreadi; Myrza Rahmanita; Sri Mariati; Nurbaeti (Jurnal Ilmiah Hospitality Management, 2026)
The Green Economy Expo 2024 (GEE 2024) promoted low-carbon practices within Indonesia’s MICE industry. However, systematic evaluation of these initiatives remains limited. This study examines the event’s carbon-related management practices, identifies internal and external strategic factors influencing sustainability performance, and formulates actionable improvement strategies. A descriptive single-case study design was employed using multi-source qualitative data, including direct observations, in-depth interviews, document analysis, and audiovisual records. To strengthen strategic assessment, a SWOT-based questionnaire was administered to 58 stakeholders, and the findings were synthesized into IFAS and EFAS matrices, followed by TOWS strategic formulation. Results indicate that participant mobility, venue energy consumption, water usage, and waste/material management were the dominant emission sources. Organizational strengths included the early establishment of a sustainability framework, development of operational standard operating procedures (SOPs), promotion of low-emission mobility, partnerships for waste sorting, and engagement of independent auditing. However, critical gaps were identified, including the absence of a verified final carbon report, incomplete post-event evaluation of Scope 3 emissions, continued reliance on single-use plastics, limited renewable energy integration, uneven staff capacity, passive sustainability education, and insufficient incentive mechanisms for stakeholders. The study proposes strengthening measurement, reporting, and verification (MRV) systems, advancing mobility and sustainable procurement interventions, and reinforcing vendor–sponsor governance structures through clear accountability and incentive frameworks. These findings contribute to the emerging discourse on sustainable event management in developing economies and provide a strategic model for advancing low-carbon transformation in Indonesia’s MICE sector.